GENDER SPECIFICS OF ANXIETY EXPRESSION AMONG FIRST-YEAR STUDENTS DURING TIMES OF WAR (Psychology Travelogs, 2023)
This article highlights the mechanism of anxiety experience among first-year students of different genders in the context of war. It characterizes the psychological foundations of the concepts «sex», «gender» and «gender specifics» of students, as well as the areas in which they manifest. The authors explore the concept of «anxiety», define its types (personal and situational/reactive anxiety) and levels. They describe conceptual theories and approaches to studying anxiety in young individuals. Psychological determinants of anxiety emergence (personal, adaptation-related, and motivational) are outlined, along with the features of its manifestation (emotional, behavioral, physiological) in young individuals. It is established that gender specifics can influence communicative behavior, professional self-realization, and emotional sphere. Gender specifics of young individuals are analyzed to identify the existing correlation between gender differences and the expression of anxiety during adolescence.To achieve the stated goal, experimental research was conducted at the Khmelnytskyi National University. The experimental sample consisted of 88 first-year students majoring in Psychology and Physical Education at the Faculty of Health, Psychology, Physical Education, and Sports, including 45 females and 43 males aged 16 to 18. The «Masculinity-Femininity» methodology by S. Bem was used to determine gender role type (androgynous, feminine, masculine), and the «State-Trait Anxiety Inventory» by Ch. Spielberger adapted by Yu. Khani was used to measure levels of personal and situational anxiety.The results of the experimental research are analyzed. It is established that gender specifics and anxiety are interdependent. The research findings underscore the relevance of the identified issue and emphasize the necessity of developing a psycho-pedagogical program to reduce anxiety levels among young individuals.
Keywords: sex; gender; gender specifics; anxiety; personal anxiety; situational anxiety; adolescence